The customer (working title) or greedy. - Woo, Pei Qi. (2013)
This report details the process of the creation of the animation short, ‘The Customer’ as a component of the author’s Final Year Project. Included are references to idea conception, the undertaking of allocated jobs, obstacles faced, and their resolutions. These have been broken up into the three major sections: pre- production, production, and post-production. Note that the project is currently in progress at the time of the writing of this report, and certain details may differ upon completion.